1994
DOI: 10.1128/aem.60.4.1374-1378.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sainfoin ( Onobrychis viciifolia Scop.) Condensed Tannins on Growth and Proteolysis by Four Strains of Ruminal Bacteria

Abstract: Sainfoin leaf condensed tannins inhibited growth and protease activity in Butyrivibriofibrisolvens A38 and Streptococcus bovis 45S1 but had little effect on Prevotella ruminicola B14 or Ruminobacter amylophilus WP225. Tannins bound to cell coat polymers in all strains. implicated the cell wall as a target of tannin toxicity. Morphological changes in B. fibrisolvens and S. bovis Condensed tannins (CTs) are generally regarded as antinutritional for ruminants because of depression of feed intake and dry matter di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
4
10

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(188 citation statements)
references
References 19 publications
10
164
4
10
Order By: Relevance
“…However, other studies have demonstrated that tannins or saponins and saponin/ tannins-containing plants have antimicrobial properties (Patra and Saxena, 2009). Inhibitory activity of tannins against bacteria has been implicated owing to the ability of tannins to form complexes with the cell wall and membrane of bacteria causing morphological changes of the cell wall and the extracellular enzymes secreted (Jones et al, 1994). Dietary supplementation did not affect methanogen, R. flavefaciens or R. albus abundances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have demonstrated that tannins or saponins and saponin/ tannins-containing plants have antimicrobial properties (Patra and Saxena, 2009). Inhibitory activity of tannins against bacteria has been implicated owing to the ability of tannins to form complexes with the cell wall and membrane of bacteria causing morphological changes of the cell wall and the extracellular enzymes secreted (Jones et al, 1994). Dietary supplementation did not affect methanogen, R. flavefaciens or R. albus abundances.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that by virtue of size, the medium-chain fatty acids are small enough to be readily dissolved in the lipid phase, to penetrate and physically disrupt cell membranes, and to inhibit enzymes involved in energy production and nutrient transfer, leading to reversible and irreversible changes that may lead to the death of the cell. Inhibition of growth of the predominant rumen bacteria by polyphenolics has been demonstrated in vitro with pure cultures (Jones et al, 1994). Although tannins can inhibit rumen micro-organisms, certain bacterial strains that are tannin-tolerant have been isolated from ruminants (Nelson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Samples of the non-cellulolytic bacterial cultures were prepared for transmission electron microscopy (TEM) as described by Jones et al (1994) at the end of the pre-expo-sure period and after 7 and 24 h of incubation with 0 or 250 mg SAP ml À1 . Filter paper residues from the extra set of cultures of cellulolytic bacteria were prepared for SEM as described by Bae et al (1993) and the preparations were viewed using H-500 (TEM) and S-570 (SEM) electron microscopes (Hitachi, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of many studies (Callaway et al, 2010;Hristov, Callaway, Lee, & Dowd, 2012;Roesch et al, 2007) (2004) reported that when rats were fed tannin diets, F I G U R E 5 Relationship between sheep and goats for ruminal ammonia-N (mg/L) concentration in response to feeding tannincontaining forages (Barry & Manley, 1984;Waghorn et al, 1987Waghorn et al, , 1990Waghorn et al, , 1998Waghorn et al, , 2002Barahona et al, 1997;Woodward and Reed, 1997;Min et al, 2002aMin et al, ,b, 2012Bengaly et al, 2007) (Jones, McAllister, Cheng, & Muir, 1994). These findings also agree with the results of a 16S-rDNA pyrosequencing study of goats fed CT extract from quebracho and chestnut tannins (Min, Solaiman, et al, 2014;Min, Wright, et al, 2014).…”
Section: Effec Ts Of Pl Ant Tannin S On Rumen Microb Iomementioning
confidence: 99%